Synthesis of Titanium Dioxide Nanoparticles for Removal of Pb2+, Cd2+ and Cr3+ from Wastewater - Mansoor, Hadeel Salah; Salman, Taghried Ali; Dhahir, Saadiyah Ahmed (Universitas Gadjah Mada, 2025)
Water pollution is widely regarded as one of the most pressing global challenges, exacerbated by human progress in industrial, agricultural, and technological sectors. Wastewater often contains non-biodegradable heavy metals that accumulate in living organisms. This accumulation poses significant risks to both environmental ecosystems and human health. The structures and surface morphology were characterized by FTIR, UV-vis measurements, XRD, SEM, and AFM. TiO2 nanoparticles could remove heavy metal ions (Pb2+, Cd2+, and Cr3+) from two samples (laboratory samples and real samples from Babylon battery factory in Al-Waziriya, Baghdad/Iraq) and measured by AAS. The results indicated that the removal percentages of heavy metal ions by TiO2 nanoparticles from real sample ions were 91.32, 64.28 and 58.33% for Pb2+, Cd2+, and Cr3+, respectively. The optimum conditions for removal were 0.1 g of TiO2 nanoparticles, 10 ppm concentration of the pollutant ions, 75 min stirring time, a 100-rpm stirring rate, and a pH level of 7. The kinetic data were related to the pseudo-second-order (R2 = 0.9455), and the isotherm models were related to the Langmuir equation (R2 = 0.9769).